Impact of myokines on chronic liver diseases: exploring the effects of metabolic dysfunction-associated steatotic liver disease (MASLD) on skeletal muscle. A narrative review - Francisco Aguirre; Mayalen Valero-Breton; Daniel Cabrera; Luis Peñailillo; María Carolina Otero; Claudia Fredes; Claudio Cabello-Verrugio (European Journal of Translational Myology)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is a condition characterized by altered liver function due to fatty accumulation, which can lead to liver inflammation and, in advanced stages, liver carcinoma. MASLD is closely linked to several metabolic alterations, such as obesity and insulin resistance, which directly affect skeletal muscles and contribute to the development of sarcopenia. Sarcopenia is the loss of muscle mass and strength, leading to decreased physical performance in severe stages. Skeletal muscles secrete molecules known as myokines under various conditions, such as exercise or diseases like MASLD. These myokines modulate communication between the skeletal muscle and other tissues. These myokines regulate muscle mass and, in pathological conditions, contribute to the development of sarcopenia. Emerging evidence highlights the crucial role of myokines in regulating skeletal muscle metabolism and function in MASLD. Myokines influence muscle metabolism, inflammation, and insulin sensitivity, offering potential therapeutic targets for managing muscle atrophy and sarcopenia in the context of MASLD. Understanding the interaction between myokines and skeletal muscle may lead to novel interventions to mitigate MASLD progression and sarcopenia. This review examines the mechanisms by which myokines regulate skeletal muscle metabolism and function in the context of MASLD.